Corporate governance rating and ownership structure in the case of Turkey - Sevin Gurarda; Emre Ozsoz; Abidin Ates (International Journal of Financial Studies, 2016)
By using corporate governance data on 22 publicly traded Turkish companies we estimate the determinants of corporate governance ratings for these companies with a focus on ownership structure. Our results show that company earnings, financial risk and firm size positively influence the corporate governance ratings (CGR) that Turkish firms receive. In the meantime, we find some weak evidence that family ownership has a negative and foreign ownership has a positive impact on CGR scores.
Keywords: G3; F3; 330; corporate governance; corporate governance index; Turkish firms